2022
DOI: 10.48550/arxiv.2206.00299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Restoring and tailoring very high dimensional spatial entanglement of a biphoton state transmitted through a scattering medium

Abstract: We report experimental results where a momentum entangled biphoton state with a giant dimensionality of 8000 is retrieved and manipulated when only one photon of the pair is transmitted through a thin scattering medium. For this purpose, the transmission matrix of the complex medium is first measured with a phase-shifting interferometry measurement method using a spatial light modulator (SLM) illuminated with a laser source. From this matrix, different phase masks are calculated and addressed on the SLM to spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…These techniques have recently been applied to highdimensional spatially-entangled photon pairs. Proof-ofprinciple experiments include their transmission through thin static [23,24] and dynamic diffusers [25], and multimode fibers [26]. However, these demonstrations have…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques have recently been applied to highdimensional spatially-entangled photon pairs. Proof-ofprinciple experiments include their transmission through thin static [23,24] and dynamic diffusers [25], and multimode fibers [26]. However, these demonstrations have…”
mentioning
confidence: 99%
“…several limits. In references [23][24][25], the authors demonstrated only the recovery of spatial correlations after the medium by performing measurements in a single spatial basis, but not entanglement itself. In reference [26], entanglement was certified at the output up to six dimensions.…”
mentioning
confidence: 99%